Individual Differences in Patterns of Community Violence Exposure and Internalizing and Externalizing Behaviors - Lambert, Sharon F. (Journal of interpersonal violence, 2021)
Youth community violence has been linked with depressive and anxious symptoms, and aggressive behavior; however, little research has examined different combinations of emotional and behavioral adjustment among community-violence-exposed youth, or individual characteristics that may account for different patterns of emotional and behavioral adjustment in community-violence-exposed youth. This research used person-centered methods to examine how gender, temperament characteristics, and prior exposure to community violence were linked with classes of community violence exposure and internalizing and externalizing adjustment among a sample of urban African American youth. Participants were 464 African American adolescents (46.7% female; mean age = 14.83, SD = .43) who reported their community violence exposure in Grade 9 and for whom reports of depressive and anxious symptoms, and aggressive behavior were available. Latent class analysis identified four classes of adolescents distinguished by their exposure to community violence exposure and internalizing and externalizing behavior. The two classes with high community violence exposure were characterized by internalizing symptoms or aggressive behavior; the two classes with low community violence exposure had low internalizing symptoms with moderate aggression or had all moderate symptoms. These community violence adjustment classes were distinguished by gender, history of community violence exposure, behavioral inhibition, and fight–flight–freeze systems. Findings highlight heterogeneity in internalizing and externalizing responses of community-violence-exposed youth and suggest factors that explain community violence exposure, repeat exposure, and responses to community violence exposure.